Evaluating provider report of fidelity to contingency management in opioid treatment programs - Casline, Elizabeth; Scott, Kelli; Murphy, Cara M.; Garner, Bryan R.; Becker, Sara J. (Drug and alcohol dependence, 2025)
With growing adoption of contingency management (CM) in addiction treatment programs, ensuring intervention fidelity over time is essential for improving patient outcomes. Nonetheless, ensuring an intervention is delivered as intended can be time- and resource-intensive for organizations. Finding ways to monitor fidelity without unduly burdening health systems is critical. This study evaluated the feasibility of using provider report to monitor CM fidelity compared to traditional observer ratings using the CM Competence Scale, leveraging data from 28 opioid treatment programs that participated in a hybrid implementation-effectiveness trial. Providers (n = 86) reported CM fidelity across 3143 sessions with observer ratings conducted for 72 of these sessions from 29 providers to assess concurrence of provider- and observer-ratings. Providers reported high fidelity for most CM practices, with high concordance with ratings from trained observers on practices that were easily observable/objective (e.g., discussing reinforcement earned in current and future session). In contrast, concordance between provider and observer ratings was lower for more nuanced practices (e.g., making connections between CM and the patients’ broader treatment and recovery goals). Overall, our findings suggest that while provider-report may effectively capture many aspects of CM delivery, discrepancies in fidelity reporting of specific CM practices warrant further investigation. Future research is needed to determine the optimal approaches for ensuring providers consistently deliver all CM elements with fidelity. •Contingency management (CM) must be delivered with fidelity to be effective.•Widespread CM implementation requires low-burden fidelity monitoring.•Provider and observer-rated CM practices were compared among opioid treatment providers.•Providers accurately reported fidelity of CM reinforcement-related practices.•Discrepancies in fidelity reporting of other CM practices warrant further inquiry.